WHY IS CAPILLAROSCOPY PERFORMED? - Davirova Gulbaxor Mamasaliyevna (Web of Journals Publishing, 2025)
Capillaroscopy is a method of visual observation of peripheral vessels. Capillary blood circulation is examined in the nail bed (area), where most capillaries are well visible. This article will give you the skills and knowledge about capillaroscopy.
Keywords: Skin electrical thermometry, Simple principle, nail layer.